2021
DOI: 10.1186/s12888-021-03493-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation of screening tools for common mental health disorders in the methadone maintenance population in Hanoi, Vietnam

Abstract: Background Common mental health disorders (CMDs), including depression, anxiety and post-traumatic stress disorder (PTSD) may worsen both HIV and drug use outcomes, yet feasible tools to accurately identify CMDs have received limited study in this population. We aimed to validate the Patient Health Questionnaire (PHQ-9), Generalized Anxiety Disorder screen (GAD-7) and Primary Care PTSD screen for DSM-5 (PC-PTSD-5) in a methadone maintenance therapy (MMT) patient population in Hanoi, Vietnam. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This finding is consistent with the finding of a study of Vietnamese cancer patients that reported 87% sensitivity and 58% specificity. 24 In contrast, other studies have suggested higher cut-off 23 a score of 7 in medical students (82% sensitivity and 71% specificity), 25 and a score of 8 in patients with epilepsy (87% sensitivity and 82% specificity). 22 Some international studies have suggested higher cut-off scores when screening for MDD in primary care, including a score of 6 (91% sensitivity and 72% specificity), 31 a score of 10 (88% sensitivity and 88% specificity), 19 and a score of 11 (83% sensitivity and 83% specificity).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This finding is consistent with the finding of a study of Vietnamese cancer patients that reported 87% sensitivity and 58% specificity. 24 In contrast, other studies have suggested higher cut-off 23 a score of 7 in medical students (82% sensitivity and 71% specificity), 25 and a score of 8 in patients with epilepsy (87% sensitivity and 82% specificity). 22 Some international studies have suggested higher cut-off scores when screening for MDD in primary care, including a score of 6 (91% sensitivity and 72% specificity), 31 a score of 10 (88% sensitivity and 88% specificity), 19 and a score of 11 (83% sensitivity and 83% specificity).…”
Section: Discussionmentioning
confidence: 77%
“…19 In PHCs, the PHQ-9 is easy to administer with outstanding discriminatory performance and accurate psychometric properties. 20 The Vietnamese PHQ-9 has been validated in sexual minority women, 21 patients with epilepsy, 22 patients undergoing methadone therapy, 23 patients with cancer, 24 and medical students. 25 It has good internal consistency, with a Cronbach's alpha of 0.81 for medical students and 0.86 for sexual minority women.…”
Section: Introductionmentioning
confidence: 99%
“…The insight that population characteristics can affect responses to study measures has motivated validation studies of screening measures in different populations. 34 , 35 Thus, while the relatively high prevalence of depressive symptoms, anxiety and stress in persons with NTDs could reflect the mental health burden in this population, it could also be due to the artifact of the screening tools. The SRQ, developed by the World Health Organization (WHO), screens for the presence of mental disorders in patients contacting primary healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire comprised the following five parts: (1) demographic characteristics including age, gender, height, weight, history of H. pylori infection and eradication (yes/no); (2) lifestyle habits covering breakfast habits, time for studying, extracurricular activities (yes/no), smoking (yes/no), alcohol intake (yes/no), living alone (yes/no); (3) sleeping habits including sleep timing, sleep duration, self-assessment of sleep quality (good/poor); (4) gastrointestinal symptoms including regurgitation, heartburn, epigastric pain, epigastric burning, postprandial fullness, early satiation, recurrent abdominal pain related to defecation or change in frequency or form of stool, the frequency and duration of these symptoms; and (5) mental health status evaluated by Generalised Anxiety Disorder Assessment (GAD-7) and Patient Health Questionnaire-9 (PHQ-9) scales, respectively. In this questionnaire, we used the Vietnamese versions of GAD-7 and PHQ-9, which have been validated in the Vietnamese population in previous studies [8,9].…”
Section: Questionnaire Designmentioning
confidence: 99%